Attitude of Acehnese Students Toward English Learning - Hendra Heriansyah Heriansyah; Diana Fauzia Sari; Khansa Aisyahrani (Journal of linguistics, culture and communication, 2026)
Having a positive attitude is a fundamental aspect that affects students’ success in the learning process. The purpose of this study is to describe Acehnese students’ attitudes toward English learning in terms of knowledge, emotion, and behavior. This study employed a descriptive qualitative study. 30 students from the seventh grade of SMPN 1 (Junior High School), Darul Imarah, the Greater Aceh regency, participated in this study. The data were collected using a questionnaire and an interview. The findings of questionnaire analysis showed students attained useful knowledge and information, felt thrilled, and were well encouraged when learning English. The interview analysis revealed that female students have a more positive attitude than male students in learning English. The interesting finding from this study is that the positive attitudes of research participants do not always have a good impact on students’ English learning outcomes. Students who give good responses to English learning, but they get low scores. Conversely, those who have negative responses; they have high scores in English learning. It indicates that between students’ attitude and their learning outcome toward English learning, do not correlate one another. This study brings both theoretical and practical implications for further research investigations about how the attitude positively affects students’ English learning achievement. The findings of the present study suggest that the forthcoming studies may probe other factors that have a mutual relationship between attitude and learning outcomes.